PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA HINDU SISWA KELAS IX - Putu Arista Sukma Dewi; Ni Luh Purnamasuari Prapnuwanti; Ni Rai Vivien Pitriani (Padma Sari: Jurnal Ilmu Pendidikan, 2026)
This study aims to determine the effect of the implementation of the Merdeka Curriculum on the learning outcomes of ninth-grade students in Hindu Religious Education at SMP Negeri 3 Singaraja. This research is motivated by the fact that the implementation of the Merdeka Curriculum in practice still faces various challenges, even though the school has fully implemented the curriculum at all grade levels. This study employs a quantitative approach. The sample consists of 47 ninth-grade students who are divided into an experimental class (24 students) and a control class (23 students). The implementation of the Merdeka Curriculum is carried out through student-centered learning, including the application of the Discovery Learning model. The focus of this study is to measure the impact of the Merdeka Curriculum on student learning outcomes, while the learning model is used as a treatment to examine how the curriculum is implemented in different contexts. Data were collected through observation, documentation, and learning outcome tests. The data were analyzed using an independent sample t-test. The results show that there is a significant effect on student learning outcomes (p < 0.05). These findings indicate that the implementation of the Merdeka Curriculum, which promotes student activeness and learning independence, contributes positively to the improvement of student learning outcomes. Furthermore, the results suggest that optimizing the implementation of the Merdeka Curriculum can be an effective strategy to improve the quality of both the learning process and learning outcomes in schools.